PENERAPAN CURRENT COST ACCOUNTING SEBAGAI SUPLEMENTARY REPORT DALAM LAPORAN KEUANGAN UNTUK MENILAI ASSET PERUSAHAAN (STUDI KASUS PADA CV. LINTANG LIMO GRESIK) - Teguh Wahyudi (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2016)
Inflation has become a fact of economic and experienced almost all countries , both developed countries or developing countries . Indonesia has experienced inflation to reach 650 % in 1965 and over 100 % in 1977 , whereas in 2013 inflasi rate dropped to 8.38% . Factors that were significantly associated with the occurrence of inflation is the price level , because the situation can be described as the tendency of information value of money decreases , followed by rising prices of goods and services compared to the original price in the same market . For the company as one of the economic actors , the change in price will affect the matters relating to the assets and liabilities . Where to more clearly see the effect of the change in the price of assets and liabilities , the company can perform grouping by monetary items are items that are affected by inflation . Changes in the price level due to inflation will affect the stability of the financial unit . This can cause difficulties if the measurement is based on the historical cost so it is necessary to include a historical cost financial statements are presented with additional information or supplementary report . . The supplementary report , a financial report which has accounted for the change in the price level . Concepts used to solve the problem of presentation of financial information by a change in the price of the current cost accounting concepts . The method used is comparative . " Application of Current Cost Acounting As a Supplementary Report In Financial Statements For Assessing Asset Company ". Financial statements to assess the company's assets after using the current method of cost Accounting experience the benefits of storage ( holding gains ) . So that it will be used as consideration for decision making and business owners interested parties .